A Disruptive Innovation perspective on students' opinions of online assessment - Michael Flavin (Association for Learning Technology, 2021)
This article analyses students' thoughts and feelings about online assessment. This article uses Disruptive Innovation theory as a lens through which to analyse students' responses to online assessment, in a case study of a Leadership course. The sources of data for this article comprise annual course evaluation surveys, a one-off assessment survey and a focus group. Qualitative content analysis with a directed approach is used to analyse the data. The results show students are capable of undertaking a range of online assessments but are, in general, reluctant to utilise the innovative possibilities of different forms of online assessment. This article adds to our understanding of online assessment by placing it within a distinct theoretical framework, offering explanations for why students may not be seeking-out innovative forms of assessment.